Pelatihan Penggunaan Sensor Waktu Untuk Menentukan Percepatan Gravitasi Bumi di SMA Islam Diponegoro - Muhammad Sayyadi; Moh Ahsan (CV. Multi Kreasi Media, 2025)
The use of practical methods is a mandatory requirement in science learning. The community service activities were carried out at SMA Islam Diponegoro, located in Wagir District, Malang Regency. This community service activity aims to provide training for students to determine the acceleration due to gravity with the help of a time sensor. As a result of the community service activities, students were able to find the value of gravitational acceleration with an error of less than 10%. Students were enthusiastic and motivated by this training activity.